Obraz heretyka w Liber apotheosis Aureliusza Prudencjusza Klemensa - Pyzik-Turska, Małgorzata (Vox Patrum, 2018)
This article attempts to show the image of heretics in early Christian poetry. There are presented most characteristic speeches Aurelius Prudentius Clemens – Spanish poet from the turn of the fourth and fifth centuries, contained especially in the Liber Apotheosis and concerning the problem of derogation from the orthodox faith. The sources of heresy are widely discussed as well as all specific vocabulary, which is mostly negatively marked.